A Homotopy Continuation Algorithm Based on Improving Path tracking and Application in the Mechanism Problems - 孙平; 严静; 陈永 (Jixie chuandong)
An improved homotopy continuation algorithm based on improving homotopy path tracking is proposed in this paper.The improved algorithm can avoid the phenomenon of resolution omission of present homotopy continuation method in solving deficient polynomial systems.The homotopy continuation method with the improved algorithm for path tracking has been used in solving the mechanism problems sucessfully.